Numerical Research on Relocation Behavior of Melt Debris Flow-in Sodium-cooled Fast Reactor - WANG Dong;GE Kui;ZHANG Yapei;HU Liang;SU Guanghui;QIU Suizheng;TIAN Wenxi (Yuanzineng kexue jishu, 2023)
After core meltdown of the sodium-cooled fast reactor (SFR), the jet of molten corium interacts with liquid sodium, which is called molten fuel-coolant interaction (MFCI). The molten corium is fragmented and solidified. The formed debris is then relocated on the core catcher or in the lower head to form debris bed. The morphological structure of the debris bed has an important influence on the cooling characteristics. However, due to the opacity of liquid sodium, it is difficult to investigate the relocation behavior of melt debris flow through experiments. In this paper, a CFD-DEM coupling model was established to simulate the relocation behavior of melt debris flow. The model was validated by experimental data. Then, the relocation behavior of UO2 melt debris was simulated, and the effect of debris diameter was studied. The liquid sodium has an effect of stiction on the front of debris flow, forming a mushroom like shape which becomes smaller as the diameter of the debris increases. The liquid sodium near the central axis is most obviously affected by the debris flow, and the velocity of the liquid sodium reaches the maximum value at the upper position of the debris catcher. As the debris diameter increases, the velocity gradient and peak velocity of the liquid sodium decrease, and the vortices formed in the vicinity of debris catcher intensify, contributing to the diffusion of momentum and energy. For different debris diameters, after the debris flows are immersed into liquid sodium, the front motions tend to converge. Then, the debris flow reaches the catcher with a nearly uniform velocity. The projection curve of the top surface of the debris bed satisfies the sine function. The accumulation angle of the debris bed with debris diameter of 1.5 mm is smaller than that of 2.0 mm and 2.5 mm. Thus the porosity of the debris bed is reduced, which is less conducive to the cooling by natural circulation. The debris temperature varies little in the argon atmosphere, while drops sharply at the moment of immersion into liquid sodium. With the increase of debris diameter, the cooling effect of the liquid sodium on the debris flow is enhanced, and the average temperature drop rate of the debris flow decreases due to reduced release rate. This study can provide a guidance for the research on the cooling characteristics of core debris bed, and has a reference value for the design and arrangement of core catcher and the formulation of other mitigation measures of severe accident in SFR.